Workplace Violence in County Hospitals in Eastern China: Risk Factors and Hospital Attitudes - Wang, Shaolan (Journal of interpersonal violence, 2021)
Workplace violence (WPV) against health workers is a public concern worldwide. Yet little is known about WPV in Chinese county level hospitals and its risk factors. The current study aimed to examine the prevalence of and the risk factors of WPV in county hospitals. A total of 1,388 health workers were interviewed in eight county hospitals in four counties of Zhejiang Province. Results indicated that 7.8% of participants suffered physical attacks and 21.2% suffered physical threats, 51.6% experienced or witnessed Yi Nao (medical disturbance created by gangs using extreme means to obtain compensation from a hospital) at least once in the past year. Physical attacks were seen significantly more in physicians (10.9%) than in nurses (5.9%). Physicians were threatened at 27.1%, followed by nurses at 20.2%. Compared with general medicine, health workers working in emergency were significantly more likely to suffer physical attacks (odds ratio [OR] = 2.7, 95% confidence interval [CI] = [1.4, 5.2], p < .01) and WPV (physical attacks or threats; OR =2.5, 95% CI = [1.6, 4.1], p < .001). Being encouraged to tolerate WPV was correlated with physical attacks (OR = 6.1, 95% CI = [3.5, 10.4], p < .001) and WPV (OR = 6.7, 95% CI = [4.6, 9.8], p < .001). Health workers in county hospitals were vulnerable to encounter WPV. This highlights the need for a focused systematic prevention concerning health workers’ safety and governmental regulations and the need for hospitals to encourage their employees to report the WPV.